Possible accumulation of emerging contaminants of concern in treated wastewater on the soil plant system of a processing tomato-wheat succession - Giuseppe Gatta; Federica Carucci; Anna Gagliardi; Michele Perniola; Michele Denora; Francesco De Mastro; Gennaro Brunetti; Sapia Murgolo; Cristina De Ceglie; Alfieri Pollice; Marcella Michela Giuliani (Agricultural Water Management)
Treated wastewater (TWW) is increasingly recognized as a valuable resource for agriculture and water management in the Mediterranean region. However, its use can pose significant risks due to the potential presence of emerging contaminants of concern (ECCs), including personal care products, pesticides, food additives, and pharmaceuticals. This study aimed to evaluate the impact of irrigation with TWW on the accumulation of ECCs within the soil-plant system during a processing tomato (Solanum lycopersicum L.)-durum wheat (Triticum turgidum spp. durum) crop succession. The experiment was carried out on Petrocalcic Palexerolls soil. Over two experimental years, both crops were irrigated using two water sources: TWW and freshwater (FW) as a control. Of the 17 compounds detected in the TWW, only 8 were found in the soil (clarithromycin, carbamazepine, fluconazole, climbazole, flecainide, sitagliptin, telmisartan and venlafaxine). The use of TWW effluent led to a significant increase in the soil of carbamazepine up to 3.3 ± 0.5 ng g−1, sitagliptin up to 9.4 ± 0.4 ng g−1, flecainide up to 8.3 ± 1.6 ng g−1, and clarithromycin up to 5.3 ± 0.6 ng g−1, highlighting their potential accumulation during the two tomato-wheat cycles. Crop uptake varied depending on the specific ECC, with different levels detected in plant roots, leaves, and stems. Importantly, no ECCs were detected in the edible parts of either crop, with concentrations below the limit of quantification. These findings underscore the potential of using TWW for irrigation without compromising food safety in crops like tomatoes and durum wheat. However, continued monitoring and further research are essential to fully understand the long-term effects of ECCs on agricultural systems and ensure the protection of both human health and the environment.